Implementasi Kebijakan Penanganan Kekerasan Dalam Rumah Tangga (KDRT) oleh Unit Perlindungan Perempuan dan Anak (PPA) Polres Lahat - Resty Seftiany; Kasman Kasman (Fakultas Ekonomi Universitas Prof. Dr. Hazairin, SH. Bengkulu, 2026)
Abstract. Domestic Violence (KDRT) remains a serious violation of human rights with significant impacts, particularly on women and children. The Indonesian government has established Law Number 23 of 2004 on the Elimination of Domestic Violence as the legal basis for handling such cases, with the police playing a crucial role in policy implementation. This study aims to analyze the implementation of domestic violence handling policies by the Women and Children Protection Unit (PPA) of Lahat Police Resort and to identify supporting and inhibiting factors affecting its implementation. This research employs a qualitative method with a descriptive approach. Data were collected through in-depth interviews, observation, and documentation. Policy implementation was analyzed using Edwards III’s framework, which includes communication, resources, disposition, and bureaucratic structure. The findings indicate that the implementation of domestic violence handling policies by the PPA Unit of Lahat Police Resort has generally followed existing regulations but has not yet been fully optimal. Major obstacles include limited resources, victims’ reluctance to report cases, cultural influences and social stigma, as well as difficulties in evidence collection. This study recommends strengthening institutional resources, enhancing policy socialization, and improving cross-sector coordination to increase the effectiveness of domestic violence handling and victim protection.